Controllable synthesis of 3D hierarchical Co3O4 nanocatalysts with various morphologies for the catalytic oxidation of toluene. Issue 2 (12th December 2017) - Ren, Quanming; Mo, Shengpeng; Peng, Ruosi; Feng, Zhentao; Zhang, Mingyuan; Chen, Limin; Fu, Mingli; Wu, Junliang; Ye, Daiqi
Abstract : Morphology plays an important role in the physicochemical properties and catalytic activity of Co3 O4 catalysts. Abstract : Three-dimensional (3D) hierarchical Co3 O4 nanocatalysts with different morphologies and various exposed crystal planes were synthesized via a hydrothermal process without the use of a cobalt surfactant precursor and subsequent direct thermal decomposition. The morphologies obtained include 3D hierarchical cube-stacked Co3 O4 microspheres (C sample), 3D hierarchical plate-stacked Co3 O4 flowers (P sample), 3D hierarchical needle-stacked Co3 O4 double-spheres with an urchin-like structure (N sample), and 3D hierarchical sheet-stacked fan-shaped Co3 O4 (S sample), which exhibit high efficiency for the total oxidation of volatile organic compounds (VOCs). Among them, the C sample exhibits the best activity with the temperature required for achieving a toluene conversion of 90% ( T 90% ) of approximately 248 °C and the activity energy ( E a ) of 80.2 kJ mol −1, which is at least 32 °C lower than that of the S sample with a higher E a of 114.9 kJ mol −1 at a space velocity (WHSV) of 48 000 mL g −1 h −1 . The effects of morphology on the physicochemical properties and catalytic activity of the Co3 O4 catalysts are investigated using numerous analytical techniques. It is concluded that the large specific surface area, highly defective structure with abundant surface adsorbed oxygen species and rich high valence Co ions in the C sample are responsible for its excellent catalytic performance. Moreover, no significant decrease in catalytic efficiency is observed over 120 h at 255 °C on the C sample, which indicates that it exhibits excellent stability for toluene oxidation. Therefore, it shows potential as a non-noble catalyst in practical applications.